Isolation, identification, molecular docking analysis, and cytoprotection of seven novel angiotensin I-converting enzyme inhibitory peptides from miiuy croaker byproducts-swim bladders - Zhu, Wang-Yu; Wang, Yu-Mei; Suo, Shi-Kun; Zheng, Shuo-Lei; Wang, Bin (Frontiers in Marine Science, 2022)
For efficiently utilizing the processing byproducts of miiuy croaker to prepare novel angiotensin I-converting enzyme (ACE) inhibitory (ACEi) peptides, in vitro gastrointestinal (GI) digestion method was screened and employed to prepare swim bladder hydrolysate with the highest ACEi activity. Subsequently, seven novel ACEi peptides were isolated from the hydrolysate and identified as DEGPE, EVGIQ, SHGEY, GPWGPA, GPFGTD, SPYGF, and VIGPF with molecular weights of 545.49, 544.58, 591.55, 583.63, 592.59, 569.60, and 531.63 Da, respectively. SHGEY and SPYGF exhibited remarkable ACEi activity with IC50 values of 0.86 ± 0.12 and 0.37 ± 0.06 mg/mL. Molecular docking experiment illustrated that the significant ACEi activity of SHGEY and SPYGF with the affinity of -8.7 and -9.7 kcal/mol mainly attributed to effectively combining with the ACEi active sites by hydrophobic interaction, electrostatic force and hydrogen bonding. Moreover, SHGEY and SPYGF could significantly up-regulate the nitric oxide (NO) production and decrease the endothelin-1 (ET-1) secretion in human umbilical vein endothelial cells (HUVECs), but also abolished the negative impacting of norepinephrine to the levels of NO and ET-1. Furthermore, SHGEY and SPYGF showed significant protection to HUVECs against H2O2 damage by increasing superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) activity to lower the contents of reactive oxide species and malondialdehyde. Consequently, ACEi peptides derived from miiuy croaker swim bladders, especially SHGEY and SPYGF, are health-promoting ingredients for functional products as a supplementary treatment to hypertension and cardiovascular diseases.